Linking the Presence of Macular Oedema to Structural and Functional Alterations in Retinitis Pigmentosa - Friesacher, Anna; Lopez Torres, Lisette T.; Valmaggia, Christophe; Rüesch, Reinhard; Todorova, Margarita G. (Klinische Monatsblätter für Augenheilkunde, 2021)
Objective To investigate the association between the central retinal thickness (CRT), the retinal nerve fibre layer thickness (RNFL), and the functional alterations in retinitis pigmentosa (RP) patients.Methods Forty-three patients with typical RP and nineteen age-matched controls, who underwent SD-OCT (macular and optic disc OCT protocols) and electrophysiology, were included. The RP group was divided into two subgroups: with clinical appearance of macular oedema (ME-RP; 30 eyes) and without macular oedema (no-ME; 44 eyes). Central retinal thickness OCT data were averaged in three zones (zone 1 [0°–3°], zone 2 [3°–8°], and zone 3 [8°–15°]) and were evaluated in relation to the RNFL thickness and electrophysiological data.Results The ME-RP group showed increased CRT (zone 1) and RNFL thickness compared to the controls and no-ME-RP (p ≤ 0.002). The no-ME-RP group had reduced CRT thickness (all zones; p ≤ 0.018) compared to the controls and ME-RP, whereas the RNFL thickness in the no-ME-RP group was reduced only compared to the ME-RP group (p < 0.001). The ME-RP group showed significantly more attenuated functional responses than the no-ME-RP patients. A significant positive interaction was found between the CRT (zones 1 and 2) and the RNFL thickness within ME-RP (p ≤ 0.010). Significant negative interactions were found between CRT, RNFL thickness, and functional findings within ME-RP (p ≤ 0.049).Conclusion The presence of macular oedema correlated well with increased RNFL thickness and residual function in RP patients. Such association provides evidence of an underlying transneuronal mechanism of retinal degeneration. Simultaneous monitoring of CRT and RNFL thickness may help in the future to evaluate the progression of the disease and the efficacy of treatments in RP patients.
Keywords: macular oedema; optical coherence tomography; retinitis pigmentosa; central retinal thickness; retinal nerve fibre layer thickness; retinal function